Asma y alergia tuberculosa: tuberculinoterapia - Ruera, Juan (1941)
He exposes in big strokes bronchial asthma clinical forms. He stops in some concepts of physiopathology and he studies the complex problem of primal phenomenons, from which derive all the symptomatology that characterize asthma accesses. He studies neurovegetative system behaviour in the origin of the asthma crisis and he declares that the vague-sympathetic unstable equilibrium helped by an occasional modality, determines a serie of short and long reflex, combined and co-ordinated that produce spasmodic secretory and vasemotor phenomenons, besides the disturbances of respiratory rhythm and other of general order.